Albumin-Fusion Recombinant FIX in the Management of People with Hemophilia B: An Evidence-Based Review - Pasca S; Zanon E (Drug Design, Development and Therapy, 2022)
Samantha Pasca,1,2 Ezio Zanon3 1Biomedical Sciences Department (DSB) - Padua University Hospital, Padua, Italy; 2Medicine Department (DIMED) - Padua University Hospital, Padua, Italy; 3Hemophilia Center, General Medicine - Padua University Hospital, Padua, ItalyCorrespondence: Samantha Pasca, Medicine Department (DIMED) – Padua University Hospital, Via Giustiniani, 3, Padua, 35128, Italy, Tel +39-339-6552395, Email sampasca27@gmail.comAbstract: Albutrepenonacog-alfa (Idelvion®, CSL Behring) is a recombinant fusion protein in which the recombinant FIX (rFIX) links a recombinant human albumin, extending the half-life of rFIX even beyond 100 hours. In 2016, this drug was approved worldwide for the treatment of pediatric and adult persons with hemophilia B (PWH-B). Its efficacy and safety were described in the PROLONG-9FP program and subsequently confirmed in the real-world practice, even if to date there are not many manuscripts that extensively and completely deal with the use of albutrepenonacog-alfa in daily practice, also evaluating its impact on the quality of life of patients treated with this drug; this review therefore aims to analyze all the publications currently available regarding the real-world use of this extended half-life concentrate, also noting which topics need further study and research.Keywords: hemophilia B, recombinant FIX, albutrepenonacog-alfa, albumin-fusion proteins, extended half-life concentrates